2020
DOI: 10.1186/s40317-019-0190-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PIT tag retention, growth and post-tagging survival in juvenile lumpfish, Cyclopterus lumpus

Abstract: Background: Passive integrated transponder (PIT) tags are used to study the movement and behaviour in populations of a wide variety of fish species and for a number of different applications from fisheries to aquaculture. Before embarking on long-term studies, it is important to collect information on both short-and medium-term survival and tag retention for the species in question. In this study, 90 juvenile lumpfish (10-20 g, 30 fish per replicate tank) were implanted with 12.5-mm FDX PIT tags. Results: Tag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…Over recent decades, passive integrated transponder (PIT) tags have frequently been used in fish ecology and fisheries research. PIT tags have relatively small size, low cost, relatively high retention (D'Arcy et al ., 2020; Foldvik & Kvigendal, 2018; Šmejkal et al ., 2019) and in most cases few adverse effects on the tagged fish ( e.g ., Hühn et al ., 2014; Skov et al ., 2005, 2020), especially when the tag‐to body‐mass ratio is low (Larsen et al ., 2013). Still, evidence suggests that capturing an animal in the wild is stressful and marking or tagging can exacerbate the situation (Gibbons et al ., 2004).…”
Section: Figurementioning
confidence: 99%
“…Over recent decades, passive integrated transponder (PIT) tags have frequently been used in fish ecology and fisheries research. PIT tags have relatively small size, low cost, relatively high retention (D'Arcy et al ., 2020; Foldvik & Kvigendal, 2018; Šmejkal et al ., 2019) and in most cases few adverse effects on the tagged fish ( e.g ., Hühn et al ., 2014; Skov et al ., 2005, 2020), especially when the tag‐to body‐mass ratio is low (Larsen et al ., 2013). Still, evidence suggests that capturing an animal in the wild is stressful and marking or tagging can exacerbate the situation (Gibbons et al ., 2004).…”
Section: Figurementioning
confidence: 99%
“…While other locations for PIT tag implantation have been described for certain fisheries species (Parker & Rankin, 2003), our data indicate that the epaxial muscle (most teleosts and sharks), the pectoral fin muscle (rays), and the lateral tail base ( Ostraciidae ) are safe and effective sites for tagging. While a tag can be lost through the skin and muscle defect at the insertion site, or the tag can migrate and be expelled from other parts of the body (Smyth & Nebel, 2013), retention rates of 99%, 100%, and 88% were reported for Chinook salmon ( Oncorhynchus tshawytscha ) (Dare, 2003); lumpfish ( Cyclopterus lumpus ) (D'Arcy et al, 2020); and lemon sharks ( Negaprion brevirostris ) (Feldheim et al, 2002), respectively. In the present study, there were two cases of tag failure or loss, and one case of confirmed loss, thus a retention rate of 99.59%.…”
Section: Discussionmentioning
confidence: 99%
“…Given the 0.57 mm opening made by the injection needle, a 1 mm difference in the tag length may, indeed, significantly affect tag loss probabilities. Internal tag retention rates are influenced by several factors, including species behaviour, individual size, life-history traits, tag size, angle and zone of insertion, and improper tagging techniques (Guy et al 1996, Gianasi et al 2015, Omeyer et al 2019, D'Arcy et al 2020. The encapsulation or rejection of internal tags is well described in fish (Gheorghiu et al 2010), sea cucumbers (Purcell et al 2006) and starfish (Olsen et al 2015), and the main reason for internal tag loss in sea urchins is probably their exit through the opening made by the needle in the first days after injection, since the lesion is expected to heal within a few days (Sonnenholzner et al 2011).…”
Section: Tag Retentionmentioning
confidence: 99%
“…In particular, experiments with PIT-tags report tag loss in the first five days (Lauzon-Guay and Scheibling 2008). In this context, a tagging needle with a nominal outer diameter that is as low as possible should always be favoured, thus promoting higher tag retention(D'Arcy et al 2020).…”
mentioning
confidence: 99%